The “Baby” Motive in the Lyric Theme of M.Tswetaewa’s Book “After Russia” (Alexander Bakhrakh – the second withoutseeing correspondent of 1923’ verses) - GEVORGYAN, TATYANA (Bulletin of Yerevan University H: Russian Philology, 2021)
The article studies a collection of Tsvetaeva’s poems addressed to Alexander Bakhrakh in the context of the poems' close connection to the development of the lyric theme throughout her book After Russia and her letters and notes from the summer and autumn of 1923. The context also encompasses her poems to other addressees (B. Pasternak and A. Shteiger) and her 1926 long poem An Attempt on a Room. The following poems are given particularly close treatment in the analysis: Over Long Distance, Curtain, An Incline, A Shell, and the first part of The Hour of the Soul cycle.
Keywords: Sybil, “motherhood of a rock”, wall, curtain, spatial decision of verses, nonformal cycle